Chasse aux otariidés et aux mustélidés - Jimena Torres; Víctor Sierpe; Manuel San Román; Marcelo Mayorga (Les Nouvelles de l’Archéologie, 2022)
This study seeks to determine the role and cultural significance of otariids and mustelids in the historical and cultural evolution of the Strait of Magellan, at the southern tip of South America. The geographical location of this inter-oceanic corridor not only allowed the passage of European navigators with geopolitical and commercial ambitions from the beginning of the 16th century, but also made possible the exchange, transmission and transformation of knowledge about the sea.Our research focuses on the hunting of pinnipeds and otters with a broad temporal approach, taking into account archaeozoological evidence from occupation sites dating from around 7,500 years ago to recent times. Historical data on the activity of foreign seal-skinners in the late 18th and early 19th centuries in the waters of the Strait of Magellan were also taken into account, at a time when the overexploitation of sea lions was having an impact on the demography of pinnipeds and, consequently, on marine ecosystems. The archaeological study shows that, despite the fact that this type of hunting was an important economic resource from the earliest occupations of canoeing or marine nomadic Indians, there are cultural periods in which it played a less prominent role than seabird hunting or fishing (ca. 3200 to 2300 BP). This suggests that its importance for the subsistence of these human groups is not constant, perhaps due to factors that we do not know today related to environmental changes and/or cultural phenomena.Finally, we have been able to observe the evolution of the role played by pinnipeds and otters in the indigenous socio-cultural context, which from being a vital resource, necessary for food, shelter and habitation, became, over the course of the 18th and 19th centuries, a commodity destined for inter-ethnic trade and commerce. This development will have major repercussions for these societies.